Multi-layer composite structure active fragment and preparation method thereof
By adopting a multi-layer composite structural design in the active fragment, the active components and high-density components are alternately stacked, and the existing active fragment density, strength and energy release efficiency are solved through metallurgical combined process, and high-performance active fragments are achieved.
Patent Information
- Application Number
- CN202510101533.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-18
AI Technical Summary
The existing active fragments are prepared by powder sintering, and there are problems such as difficulty in reaching the theoretical value of density and strength, difficulty in regulating brittleness and fragmentation, and early release of the active element, resulting in insufficient release of energy.
The multi-layer composite structure design is adopted to alternately stack and arrange the active component material sheets and high-density structural component material sheets, and are prepared by metallurgical combination, using cover hot pressing, stacking or hot isostatic pressing processes to ensure metallurgical bonding between the sheets.
High-density and high-intensity active fragmentation are achieved, while avoiding the early release of the active element. After invasion, it can be fully fragmented and released, and high-performance active fragmentation can be obtained.
Smart Images

Figure CN119840249A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of warhead active fragments, and in particular relates to a multi-layer composite structure active fragment and a preparation method thereof. Background Art
[0002] Fragments are the basic damaging unit of a lethal warhead. As traditional inert fragments mainly rely on a single kinetic energy to kill targets, the phenomenon of "hitting but not destroying" sometimes occurs. In order to improve the lethality of fragment warheads, active fragments were born. Active fragments will quickly produce a burning or explosion effect while penetrating the target at high speed, causing greater damage to the target.
[0003] Based on the above application requirements, the ideal active fragments need to have high density and strength to penetrate the target shell; at the same time, the material needs to have high enough activity to be fully fragmented inside the target, burning or exploding to release a large amount of energy and completely destroy the target. However, active fragments are currently prepared by powder sintering. The fragments prepared in this way are limited by the characteristics of the powder sintering process itself, and there are problems such as density and strength that are difficult to reach the theoretical value, brittleness and fragmentation that are difficult to control, and insufficient energy release. For example, increasing the sintering temperature can increase strength and density, but it will cause the active elements to release energy prematurely, the fragmented particles to be larger, the activity to be poor, and the energy release to be insufficient; while lowering the sintering temperature is beneficial to activity retention and release, it will lead to problems of low strength and density. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a multi-layer composite structure active fragment and its preparation method. The present invention proposes a new active fragment structure. Compared with the traditional active fragment prepared by powder sintering, the active components and high-density structural components are arranged in an alternating stacked structure. This structure can avoid the problems of low density and strong plasticity and premature reaction of active components in the powder sintering method. The present invention realizes the full fragmentation of the fragment after penetration and the release of a large amount of energy through the stress-strain interaction between the active components and the high-density structural components.
[0005] The present invention is specifically implemented through the following scheme.
[0006] The present invention provides a multi-layer composite structure active fragment, wherein the multi-layer composite structure active fragment is composed of active component material layers and high-density structural component material layers alternately stacked, and the layers are metallurgically bonded.
[0007] The active material in the active component material layer is one or more of a metal element, a metal oxide, a metal fluoride polymer and a metal hydride, wherein the metal is Al, Cr, Mg, Mn, Ti, Zr, Fe, Hf or Ta.
[0008] The density of the material in the high-density structural component material sheet layer is ≥10 g / cm3.
[0009] Preferably, the thickness of each layer of the active component material sheet is 1 μm to 5000 μm.
[0010] Preferably, the material in the high-density structural component material sheet is one or more of a metal element, a metal oxide and a metal carbonitride, wherein the metal is tungsten, tantalum, nickel or lead, and the thickness of each layer of the high-density structural component material sheet is 1 μm to 5000 μm.
[0011] The present invention provides a method for preparing the above-mentioned multi-layer composite structure active fragment, which is prepared by a jacket hot pressing process, a stacking rolling process or a hot isostatic pressing process.
[0012] Preferably, the sheath hot pressing process comprises the following steps: Prepare a rigid package according to the shape of the component layers and the stacking height.
[0013] The stacked sheet material is placed in a bag, and a pressing block of the same material as the bag is placed on the sheet material; the assembled sheet material and the bag are placed in a hot pressing device for pressing; the pressed sheet material can be cut into corresponding fragment shapes.
[0014] Preferably, in the sheathing hot pressing process, the lamination method is solid sheet layers or powder bonding and laying sheet layers.
[0015] The solid-state sheet refers to an arrangement of alternating layers of active component material sheets and high-density structural component material sheets.
[0016] Powder bonding and laying of sheets refers to laying material powder of a high-density structural component material sheet on an active component material sheet, or laying material powder of an active component material sheet on a high-density structural component material sheet, mixing a binder in the powder, and then stacking the sheets with the laid powder together.
[0017] Preferably, the gap between the sheet layer and the rigid sheath is 0.001 mm to 2 mm, and the gap between the pressing block and the sheath is 0.001 mm to 0.1 mm.
[0018] Preferably, under vacuum, the hot pressing temperature is 500° C. to 1500° C., the pressure is 2 MPa to 30 MPa, and the time is 0.5 h to 30 h.
[0019] Preferably, the roll-bonding process comprises the following steps: The stacked sheet materials are placed in the steel ladle, which is required to completely cover the stacked sheet materials in all directions, and the steel ladle is welded into a whole. After the welded ladle and the stacked sheet materials inside are heated, they are put into the rolling mill for multiple passes of rolling to reduce them to the required thickness, and then the ladle is removed and the stacked and rolled sheets are cut into corresponding fragment shapes.
[0020] In the rolling process, the lamination method is solid sheet or powder bonding and laying sheet, wherein the solid sheet refers to the alternating lamination of active component material sheets and high-density structural component material sheets.
[0021] Powder bonding and laying of sheets refers to laying material powder of a high-density structural component material sheet on an active component material sheet, or laying material powder of an active component material sheet on a high-density structural component material sheet, mixing a binder in the powder, and then stacking the sheets with the laid powder together.
[0022] Preferably, after welding, the interior of the sheath is in a vacuum state.
[0023] Preferably, the rolling temperature is 500° C. to 1500° C., the single rolling reduction is 1 mm to 5 mm, and the number of passes is 1 to 5.
[0024] Preferably, the hot isostatic pressing comprises the following steps: Place the stacked sheet materials in the steel ladle, requiring the ladle to completely cover the stacked sheet materials in all directions, and weld the steel ladle into a whole. Put the welded ladle and the stacked sheet materials inside it into the hot isostatic pressing equipment for pressing. After pressing, remove the ladle and cut the pressed sheet into the corresponding fragment shape.
[0025] Preferably, in the hot isostatic pressing process, the lamination method is solid sheet layers or powder bonding and laying sheet layers; wherein the solid sheet layers refer to the alternating lamination of active component material sheets and high-density structural component material sheets.
[0026] Powder bonding and laying of sheets refers to laying material powder of a high-density structural component material sheet on an active component material sheet, or laying material powder of an active component material sheet on a high-density structural component material sheet, mixing a binder in the powder, and then stacking the sheets with the laid powder together.
[0027] Preferably, after welding, the interior of the sheath is in a vacuum state.
[0028] Preferably, the pressing temperature is 500° C. to 1500° C., the pressure is 20 MPa to 200 MPa, and the time is 0.5 h to 30 h.
[0029] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes for the first time a multi-layer composite structure active fragment, which has a structure in which active components and high-strength and high-density component metal sheets are alternately arranged, and the active fragments are prepared by forming a metallurgical bond between the sheet layers, having high density and high strength. At the same time, the active components do not react in advance to release energy during the preparation process. During the penetration process, the high-density components have a cutting and fragmenting effect on the active components, so that they can be fully fragmented after penetration and the active components can fully release energy, thereby obtaining high-performance active fragments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the sampling method on the zirconium-tungsten multilayer composite active fragment in Example 1.
[0031] Figure 2 In the figure, (a) is the organizational structure of the zirconium-tungsten multilayer composite structure active fragment material of Example 1, and (b) is the dynamic compression performance of the zirconium-tungsten multilayer composite structure active fragment material of Example 1.
[0032] Figure 3 This is the crack distribution of a certain layer cross section of the zirconium-tungsten multi-layer composite structure active fragment after dynamic compression in Example 1. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention. The experimental methods and detection methods described in the following embodiments are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.
[0034] The active fragments prepared in the prior art have problems such as density and strength that are difficult to reach theoretical values, brittleness and fragmentation that are difficult to control, premature energy release of active elements, and insufficient energy release. The present invention provides a new solution, in which active component material sheets and high-density structural component material sheets are alternately stacked to prepare multi-layer composite structure active fragments. The structure is an alternating arrangement of active components and high-strength and high-density component metal sheets, which have high density and high strength. At the same time, the active components do not react in advance to release energy during the preparation process. During the penetration process, the high-density components have the effect of cutting and fragmenting the active components, so that the active elements fully release energy after penetration, thereby obtaining high-performance active fragments. Among them, the sheets are metallurgically bonded.
[0035] The active material in the active component material layer is one or more of a metal element, a metal oxide, a metal fluoride polymer and a metal hydride, wherein the metal is Al, Cr, Mg, Mn, Ti, Zr, Fe, Hf or Ta; preferably Al and Cr.
[0036] The density of the material in the high-density structural component material sheet is ≥10 g / cm3. In a preferred embodiment of the present invention, the material in the high-density structural component material sheet is one or more of a metal element, a metal oxide and a metal carbonitride, wherein the metal is tungsten, tantalum, nickel or lead, and tungsten is preferred based on cost considerations.
[0037] In a preferred embodiment of the present invention, the thickness of each layer of the high-density structural component material sheet is 1 μm to 5000 μm. The thickness of each layer of the active component material sheet is 1 μm to 5000 μm.
[0038] The multi-layer composite structure active fragment of the present invention can be prepared by a jacket hot pressing process, a roll-on process or a hot isostatic pressing process. These processes are used to make the sheet layers metallurgically bonded. The preparation process provided by the present invention is simple and easy to implement. The prepared active fragment avoids the problems of low density and strength and plasticity and premature reaction of active elements in the powder sintering method.
[0039] The encapsulation hot pressing process includes the following steps: Prepare a rigid package according to the shape of the component layer and the stacking height; place the stacked layer material in the package, and place a block of the same material as the package on the top of the layer material; place the assembled layer material and the package in a hot pressing device for pressing; and cut the pressed sheet into corresponding fragment shapes.
[0040] In a preferred embodiment of the present invention, each component layer of the multilayer composite structure is a solid layer or a powder-bonded paving layer. The solid layer refers to the alternating arrangement of active component material layers and high-density structural component material layers. The powder-bonded paving layer refers to laying material powder of a high-density structural component material layer on an active component material layer, or laying material powder of an active component material layer on a high-density structural component material layer, mixing a binder in the powder, and then stacking the powder-laid layers together.
[0041] In a preferred embodiment of the present invention, the gap between the sheet and the rigid package is 0.001 mm to 2 mm, and the gap between the block and the package is 0.001 mm to 0.1 mm. Under vacuum conditions, the hot pressing temperature is 500°C to 1500°C, the pressure is 2 MPa to 30 MPa, and the time is 0.5 h to 30 h. The specific parameter values can be set according to the selected materials.
[0042] The roll bonding process includes the following steps: The stacked sheet materials are placed in the steel ladle, which is required to completely cover the stacked sheet materials in all directions, and the steel ladle is welded into a whole. After the welded ladle and the stacked sheet materials inside are heated, they are put into the rolling mill for multiple passes of rolling to reduce them to the required thickness, and then the ladle is removed and the stacked and rolled sheets are cut into corresponding fragment shapes.
[0043] In a preferred embodiment of the present invention, each component layer of the multilayer composite structure is a solid layer or a powder-bonded paving layer. The solid layer refers to the alternating arrangement of active component material layers and high-density structural component material layers. The powder-bonded paving layer refers to laying material powder of a high-density structural component material layer on an active component material layer, or laying material powder of an active component material layer on a high-density structural component material layer, mixing a binder in the powder, and then stacking the powder-laid layers together.
[0044] In a preferred embodiment of the present invention, the inside of the sheath is in a vacuum state after welding. The rolling temperature is 500°C to 1500°C, the single pressing amount is 1 mm to 5 mm, and the number of passes is 1 to 5. The specific parameter values can be set according to the selected materials.
[0045] Hot isostatic pressing includes the following steps: Place the stacked sheet materials in the steel ladle, requiring the ladle to completely cover the stacked sheet materials in all directions, and weld the steel ladle into a whole. Put the welded ladle and the stacked sheet materials inside it into the hot isostatic pressing equipment for pressing. After pressing, remove the ladle and cut the pressed sheet into the corresponding fragment shape.
[0046] In a preferred embodiment of the present invention, each component layer of the multilayer composite structure is a solid layer or a powder-bonded paving layer. The solid layer refers to the alternating arrangement of active component material layers and high-density structural component material layers. The powder-bonded paving layer refers to laying material powder of a high-density structural component material layer on an active component material layer, or laying material powder of an active component material layer on a high-density structural component material layer, mixing a binder in the powder, and then stacking the powder-laid layers together.
[0047] In a preferred embodiment of the present invention, the interior of the package is in a vacuum state after welding. The pressing temperature is 500°C to 1500°C, the pressure is 20MPa to 200MPa, and the time is 0.5h to 30h. The specific parameter values can be set according to the selected materials.
[0048] The above preparation method is simple, and the prepared multi-layer composite structure active fragments can have high density, high strength and high energy release activity at the same time, which is completely suitable for large-scale industrial application.
[0049] The present invention will be specifically described below by the following examples.
[0050] Example 1 The zirconium-tungsten multilayer composite active fragments were prepared by the jacket hot pressing process. The size of the zirconium metal sheet is 300 mm×300 mm×200 μm, and there are 50 pieces in total. The size of the tungsten metal sheet is 300 mm×300 mm×200 μm, and there are 50 pieces in total. The zirconium metal sheet and the tungsten metal sheet are degreased and cleaned, and a layer of zirconium sheet and a layer of tungsten sheet are arranged alternately, for a total of 100 pieces. Figure 1 100 overlapped zirconium-tungsten metal sheets were placed in the package, and a block of the same material as the package was placed on top of the sheet material. The gap between the sheet material and the package was 1 mm, and the gap between the block and the package was 0.1 mm. The temperature was kept at 1300℃ and 8 MPa stress for 240 min, and then cooled with the furnace.
[0051] The pressed multi-layer composite sheet is divided into fragments as required. The structure and compression properties of the fragments are as follows: Figure 2 As shown in (a), the dynamic compression performance sampling method is as follows Figure 1 As shown, vertical sampling, parallel sampling and 45° sampling were performed respectively, and sampling was performed twice in each direction. Figure 2 (b) shows that the fragments prepared by this method have good dynamic compression performance, reaching 1300MPa~1600MPa; and Figure 1 It shows that the good dynamic compression performance is not affected by the sampling direction, that is, the performance is not affected by the fragment impact direction during the actual impact process. The stress-strain interaction between the high-density brittle component and the high-activity plastic component forms a dense network of cracks, such as Figure 3 As shown, the fragments are fully broken during the impact process, so that the active elements of the fragments have good reaction kinetic conditions, can release a large amount of energy, and have high destructive power. The multi-layer composite structure zirconium-tungsten fragments show high strength, high density and high fragmentation activity release characteristics.
[0052] Example 2 Preparation by hot isostatic pressing, specifically: the size of the zirconium metal sheet is 300 mm×300 mm×200 μm, a total of 50 sheets, degreased and cleaned. The mixed tungsten powder and nickel powder are evenly spread on the zirconium sheet, the powder thickness is 2 mm, and the nickel-tungsten powder is mixed with a binder to ensure uniform powder spreading. Repeat the zirconium sheet powder spreading operation, and stack the 50 zirconium sheets with nickel-tungsten powder together, keeping the zirconium sheets and tungsten-nickel powder layers alternately arranged. Put the 50 overlapping zirconium and nickel-tungsten powder sheets into the steel sleeve, weld the sleeve in a vacuum electron beam welder to seal it intact; put it into the hot isostatic pressing equipment, keep it warm for 240 min at 1180℃ and 150 MPa stress, and cool it with the furnace. Take out and remove the sleeve, and divide the pressed multi-layer composite sheet into fragments as needed.
[0053] Example 3 The preparation is carried out by stacking and rolling process. Specifically, the size of the zirconium metal sheet is 300 mm×300 mm×200 μm, with a total of 50 sheets, and the sheet is degreased and cleaned. The mixed tungsten powder and nickel powder are evenly spread on the zirconium sheet, with a thickness of 2 mm. The nickel-tungsten powder is mixed with a binder to ensure uniform powder spreading. Repeat the zirconium sheet powder spreading operation, and stack the 50 zirconium sheets with nickel-tungsten powder, keeping the zirconium sheets and tungsten-nickel powder layers alternately arranged. Put the 50 overlapping zirconium and nickel-tungsten powder sheets into the steel sleeve, weld the sleeve in a vacuum electron beam welder to seal it intact; put it in a heating furnace at 1150℃ for 4 hours, and then put it into the rolling mill for 3 passes, with a reduction of 2 mm each time. After rolling, cool naturally, remove the sleeve, and divide the pressed multi-layer composite sheet into broken pieces as needed.
[0054] The active fragments prepared in Example 2 and Example 3 also have high density and high strength. At the same time, the active components do not react to release energy in advance during the preparation process. During the penetration process, the high-density components have a cutting and fragmenting effect on the active components, so that the active components fully release energy after penetration. No more details will be given.
[0055] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, they are also intended to be included.
Claims
1. A multi-layer composite structure active fragment, characterized in that: The multi-layer composite structure active fragments are composed of active component material layers and high-density structural component material layers alternately stacked, and the layers are metallurgically bonded; The active material in the active component material sheet is one or more of a metal element, a metal oxide, a metal fluoride polymer and a metal hydride, wherein the metal is Al, Cr, Mg, Mn, Ti, Zr, Fe, Hf or Ta; The density of the material in the high-density structural component material sheet layer is ≥10 g / cm3.
2. The multi-layer composite structure active fragment according to claim 1, characterized in that: The material in the high-density structural component material sheet layer is one or more of a metal element, a metal oxide and a metal carbonitride, wherein the metal is tungsten, tantalum, nickel or lead.
3. The method for preparing a multi-layer composite structure active fragment according to claim 1 or 2, characterized in that: It is prepared by using a jacket hot pressing process, a stacking rolling process or a hot isostatic pressing process.
4. The preparation method according to claim 3, wherein the sheath hot pressing process comprises the following steps: According to the shape and stacking height of the active component material sheet and the high-density structural component material sheet, a rigid package is prepared; Place the stacked sheet material in a rigid package, and place a block of the same material as the package on top of the sheet material; The assembled sheet material and the package are placed in a hot pressing device for pressing; the pressed sheet material is cut into corresponding fragment shapes.
5. The preparation method according to claim 4, characterized in that: The gap between the sheet material and the rigid package is 0.001mm~2mm, and the gap between the pressing block and the rigid package is 0.001mm~0.1mm; Under vacuum conditions, the hot pressing temperature is 500°C to 1500°C, the pressure is 2MPa to 30MPa, and the time is 0.5h to 30h.
6. The preparation method according to claim 3, characterized in that: The roll bonding process comprises the following steps: The stacked sheet materials are placed in a ladle jacket so that the ladle jacket completely covers the stacked sheet materials in all directions, and the ladle jacket is welded into a whole; the welded ladle jacket and the stacked sheet materials inside are heated and put into a rolling mill for multiple rolling to reduce them to the required thickness, and then the ladle jacket is removed and the stacked and rolled sheets are cut into corresponding fragment shapes.
7. The preparation method according to claim 6, characterized in that: After welding, the inside of the ladle is in a vacuum state; the rolling temperature is 500℃~1500℃, the single reduction is 1 mm~5 mm, and the number of passes is 1 to 5.
8. The preparation method according to claim 3, characterized in that: The hot isostatic pressing comprises the following steps: Place the stacked sheet materials in the ladle jacket so that the jacket completely covers the stacked sheet materials in all directions, and weld the ladle jacket as a whole. Put the welded ladle jacket and the stacked sheet materials inside it into the hot isostatic pressing equipment for pressing. After pressing, remove the ladle jacket and cut the pressed sheets into corresponding fragment shapes.
9. The preparation method according to claim 8, characterized in that: After welding, the inside of the ladle is in a vacuum state; the pressing temperature is 500℃~1500℃, the pressure is 20MPa~200MPa, and the time is 0.5h~30h.
10. The preparation method according to claim 4, 6 or 8, characterized in that: The stacking method is solid sheet or powder bonded sheet; The solid-state sheet refers to an arrangement of active component material sheets and high-density structural component material sheets alternately stacked; The powder bonding and laying of sheets refers to laying material powder of a high-density structural component material sheet on an active component material sheet, or laying material powder of an active component material sheet on a high-density structural component material sheet, mixing a binder in the powder, and then stacking the sheets with the laid powder together.
Citation Information
Patent Citations
Penetration blasting warhead with titanium alloy matrix containing active fragment inclusions and preparation method
CN112797852A
Composite energetic fragment containing tough outer layer and brittle inner layer and preparation method of composite energetic fragment
CN113649579A
Energy-containing laminated composite material for warhead shell and preparation method of energy-containing laminated composite material
CN117047111A
Granulation of high density tungsten-nickel-iron alloy powder
IN201941032247A
Warhead fragmenting structure of compacted fragments
US20180112960A1